The evolution of Conservative Party social policy - Williams, Ben 1973- (Palgrave Macmillan, 2015)
"Having experienced one of its worst ever general election defeats in 1997, the Conservative Party spent an unfamiliar thirteen years in opposition. During its sustained exile from national office, the party addressed perceptions of its primarily economic policy agenda, subsequently revising its position on various social issues as a result.This book identifies the key theories and ideological traditions that have shaped and influenced Conservative Party social policy-making, with specific attention given to the evolution of Conservative Party social policy from 1997 onwards. Specific ideological and practical influences that have shaped Conservative thought are systematically highlighted, while notable social policy initiatives pursued by the post-2010 government are analyzed, notably The Big Society, Free Schools, welfare reform and NHS re-organization, all framed within the context of David Cameron's depiction of a 'broken society'. Rigorous concluding judgments provide insight into how much 'change' the modern Conservative Party has initiated within these policy spheres"..